THE IMPACT OF SOCIAL MEDIA INFLUENCER MARKETING ON CONSUMER PURCHASE INTENTIONS IN EMERGING ECONOMIES (Al-Aasar, 2025)
Social media influencer (SMI) marketing has become a central lever for digital growth in emerging economies, where rapid smartphone adoption, youthful demographics, and platform-first shopping behaviors reshape the path-to-purchase. This article synthesizes contemporary evidence and theory to explain how influencer attributes (credibility, expertise, trustworthiness, attractiveness), content qualities (authenticity, informativeness, entertainment), and relational mechanisms (parasocial interaction and community identification) drive consumer purchase intentions (PI). We integrate Source Credibility Theory, the Theory of Planned Behavior, and the Stimulus–Organism–Response (S–O–R) framework into a unified model and derive testable hypotheses. Drawing on recent studies from Pakistan, India, Indonesia, Nigeria, and the MENA region, we show consistent positive effects of influencer credibility and trust on PI, frequently mediated by brand attitude, perceived value, and social brand engagement. We then propose a robust methodology blueprint tailored to emerging-market constraints and discuss ethical, policy, and managerial implications. The article concludes with directions for future research on algorithmic reach, disclosure formats, and AI-generated influencers.